Uma análise sobre a representação do corpo e das emoções em Insubmissas lágrimas de mulheres, de Conceição Evaristo - MONTEIRO, Alexandra Araujo (2023)
The object of study and general theme to be addressed in this research is the representation of the body and emotions in the work Insubmissas lágrimas de mulheres, by Conceição Evaristo. In view of this, we are guided by the following guiding question: how does the representation of the black body and its emotions occur in the aforementioned work? To this end, we have as a general objective, to analyze how the black body and its emotions are represented in the work Insubmissas lágrimas de mulheres, by Conceição Evaristo, besides, specifiedly; to verify what are the elements that contribute to the development of the representation of the body in the work in question; to investigate how the representation of the body highlights some narrative strategies of the writer; and identify how the body represented defines the characters of the work studied, and determines their actions and emotions. The research in question, from the methodological point of view (vide PRODANOV, 2013, p. 51-54), is classified as a basic research and bibliographic, in which the form of approach is qualitative. From the point of view of its objectives, research is descriptive. Thus, we use the following theoretical framework: Achille Mbembe (2018); Neusa Souza (2021);Clóvis Moura (2019); Frantz Fanon (2020);Sidney Chalhoub (2018); Beatriz Nascimento (2022); Silviano Santiago (2019); David Le Breton (2016, 2019); Maurice Merleau-Ponty (2018), among other authors. We conclude that Conceição Evaristo humanizes his characters by crossing empirical life and fiction, in order to promote a fictionalization of the real, in which black women find themselves represented in their body dimension, their emotions and experiences.